Effects of microalloying with La on microstructure and properties of cold rolled pure copper. (July 2014) - Chen, Y.; Zhang, S. H.; Cheng, M.; Song, H. W.; Xu, A. W.; Liu, J. S.
Abstract : The microstructure and mechanical properties of pure copper with microalloying lanthanum (La) addition after cold rolling and subsequent aging were investigated. Tensile tests of the aged specimens were performed to examine the effect of aging temperature and microstructure on mechanical properties. Optical microscope, scanning electronic microscope and hardness tests were used to characterise the deformation and recrystallisation behaviour, as well as microstructure evolution in the alloys. The results show that the tensile strength increases gradually with increasing La concentration, but elongation increases at first and then decreases when the addition level of La is more than 0·089 wt-%. The improvement of properties of rolled copper with proper La addition is attributed to the effect of second particle strengthening and purifying. However, overaddition of La leads to the decrease of elongation of rolled copper owing to the excessive La rich second phase. In addition, an important finding was that when the content of La is less than 0·1 wt-%, recrystallisation was inhibited, while the content of La is more than 0·1 wt-%, recrystallisation was promoted.